Increased Urine IgM and IgG2 Levels, Indicating Decreased Glomerular Size Selectivity, Are Not Affected by Dalteparin Therapy in Patients with Type 2 Diabetes. (12th February 2012) - Torffvit, Ole; Kalani, Majid; Apelqvist, Jan; Eliasson, Björn; Eriksson, Jan W.; Brismar, Kerstin; Jörneskog, Gun
Abstract : Fifty-four type 2 diabetic patients with neuroischemic foot ulcers were randomised to treatment with 5000 IU of dalteparin, (n = 28 ), or physiological saline, (n = 26 ), once daily until ulcer healing or for a maximum of 6 months. Thirty-three patients had normo-, 15 micro-, and 6 macroalbuminuria. The urinary levels of IgM and IgG2 were elevated in 47 and 50 patients, respectively. Elevated urinary levels of IgM and IgG2 indicate decreased glomerular size selectivity. Urine IgM levels were associated with IGF-1/IGFBP-1 and IGFBP-1 levels. Dalteparin treatment increased urinary levels of glycosaminoglycans (P < 0.001 ) and serum IGFBP-1 (P < 0.05 ) while no significant effects were seen in any of the other studied parameters. In conclusion, dalteparin therapy in patients with type 2 diabetes had no effects on urinary levels of albumin, IgM, or IgG2 despite significantly increased glycosaminoglycans in urine. Elevated urinary levels of IgM and IgG2 might be more sensitive markers of renal disease than albuminuria in patients with type 2 diabetes and antihypertensive therapy.